2023
DOI: 10.1002/epi4.12840
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low‐grade epilepsy‐associated tumor from implanted stereoelectroencephalography electrodes

Taylor A. Gatesman,
Jasmine L. Hect,
H. Westley Phillips
et al.

Abstract: Low‐grade epilepsy associated tumors (LEATs) are a common cause of drug‐resistant epilepsy in children. Herein we demonstrate the feasibility of using tumor tissue derived from stereoelectroencephalography (sEEG) electrodes upon removal to molecularly characterize tumors and aid in diagnosis. An 18‐year old male with focal epilepsy and MRI suggestive of a dysembryoplastic neuroepithelial tumor (DNET) in the left posterior temporal lobe underwent implantation of seven peri‐tumoral sEEG electrodes for peri‐opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Three further studies compared variant allele frequencies (VAFs) of variants identified in resected tissue samples with the VAFs in depth electrode samples from the same patients. [17][18][19] Variants that could be identified in depth electrode samples had 7-27× lower VAFs than in tissue. One explanation for the lower allele frequencies is that only a part of the depth electrode may be located within the area of interest, resulting in a dilution of the sample with healthy cells from other areas.…”
Section: Introductionmentioning
confidence: 99%
“…Three further studies compared variant allele frequencies (VAFs) of variants identified in resected tissue samples with the VAFs in depth electrode samples from the same patients. [17][18][19] Variants that could be identified in depth electrode samples had 7-27× lower VAFs than in tissue. One explanation for the lower allele frequencies is that only a part of the depth electrode may be located within the area of interest, resulting in a dilution of the sample with healthy cells from other areas.…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al used the same method to identify a mosaic gradient for a KCNT1 variant in a patient with nonlesional multifocal epilepsy 17 . Three further studies compared variant allele frequencies (VAF) of variants identified in resected tissue samples with the VAF in depth electrode samples from the same patients [18][19][20] . Across these studies, variants could be identified in depth electrode samples in four out of five patients.…”
Section: Introductionmentioning
confidence: 99%